Reoperative Parathyroid Surgery Techniques and Tips for Success (Springer International Publishing, 2018)
This text outlines the underlying reasons primary surgery for primary hyperparathyroidism may be unsuccessful as well as give tips on how to avoid this scenario. It also discusses the potential pitfalls in primary surgery that can lead to recurrent hyperparathyroidism, recognizing current localization techniques available for reoperative parathyroid surgery and their indications, and applying surgical algorithms for reoperative parathyroid surgery. Reoperative Parathyroid Surgery: Tips for Success will serve as a useful resource for physicians and trainees dealing with this type of surgery and provide a concise yet comprehensive summary of the current status of the field that will help guide patient management. .